The Windy City - Smith, Roland, 1951-; Spradlin, Michael P. (Ann Arbor, Mich. : Sleeping Bear Press, 2014)
"When Quest (Q) and his stepsister Angela head to Chicago for their parents' concert, they uncover another plot by the terrorist group Ghost Cell in the Windy City"--Provided by publisher.
4.8
5-8
660L
Keywords: Terrorism -- Juvenile fiction; Stepfamilies -- Juvenile fiction; Musicians -- Juvenile fiction; Terrorism -- Fiction; Stepfamilies -- Fiction; Musicians -- Fiction; Spies -- Fiction; Mystery and detective stories; Terrorism -- Fiction; Stepfamilies -- Fiction; Musicians -- Fiction; Spy stories; Mystery fiction; Spies -- Fiction; Terrorism -- Fiction; Stepfamilies -- Fiction; Musicians -- Fiction; Mystery and detective stories; Chicago (Ill.) -- Juvenile fiction; Chicago (Ill.) -- Fiction; Chicago (Ill.) -- Fiction; Chicago (Ill.) -- Fiction; Spy stories; Mystery fiction